Concepts and Paradigms of Islamic Education in Indonesian Islamic Boarding Schools (Study at Al-Mukmin Ngruki Islamic Boarding School) - Supriyanto; Amrin (CV. AFDIFAL MAJU BERKAH, 2022)
This study departs from the existing anxiety, Islamic boarding schools which are seen as Islamic educational institutions have different understandings in interpreting religious teachings so their actualization in society is also different. Al-Mukmin Ngruki Islamic Boarding School, Sukaharjo Regency, Central Java. As for the data collection using observation, interviews and documentation. While the analysis uses the interpretation of cohesion with the verstehen method, which is an interpretation that is attempted to explain the observed sociological phenomena by the meaning given by the object being observed. The results showed that the concept of Islamic education which was implemented by Al-Mukmin Ngruki Sukoharjo, Central Java first, both adhered to the commitment of Islamic education to tafaqquh fi al-din in creating a generation of Islamic scholars 'amilin, Muslim individuals who are by the teachings of Allah. and practice these teachings in various aspects of their lives. Second, full-time education (full day school) an educational environment that is completely total, because all activities in the pesantren environment have educational values. Third, the concept of integrative education, with a dormitory system, allows the two pesantren to develop all the potential of students gradually towards the perfection of the integrity of the Muslim personality (al-insan al-kamil), both in the cognitive aspect, affective and psychomotor. Fourth, presenting the concept of complete Islamic education (Islamic integrated education) which combines formal, in-formal and non-formal education. As an Islamic educational institution that carries the ideology of salafi-haraki basically places Islam as a way of life, the implications in the community for alumni are to follow the manhaj shalaf ash-shalih which is directed at 'izz al-Islam wa al-muslimin.